Israeli attacks on Gaza schools could be crimes against humanity: UN probe (UN News, 2025)
The Israeli military’s destruction of Gaza’s education and cultural infrastructure amount to war crimes and the crime against humanity of extermination, a UN investigative body said on Tuesday, as humanitarian agencies warned of continued mass suffering across the Strip.